Clinical and Laboratory Outcomes in HIV-1 and HTLV-1/2 Coinfection: A Systematic Review - Montaño-Castellón, Iris; Marconi, Cleyde Sheyla Chachaqui; Saffe, Clara; Brites, Carlos (Frontiers in Public Health, 2022)
Aim: To perform a systematic review to describe the available findings on clinical outcomes in HIV-1 and HTLV-1/HTLV-2 co-infected individuals since 1995. Design: This Systematic Review used PECO criteria follow by PRISMA reporting guidelines and registered as CRD42021279062 (Prospero database). The Newcastle-Ottawa Scale assessed the methodological quality of included studies. Data collection and analysis: A systematical search in PubMed/MEDLINE, Embase, Web of Sciences databases for cross-sectional, case-control, or cohort studies design to identify clinical and laboratorial outcomes related to HIV-1 and HTLV-1/2 coinfection. Search strategy: ((“HIV-1” AND “HTLV-1” OR “HTLV-2”) AND (“Coinfection”) AND (1990/01/01:2021/12/31[Date- Publication])). Results: A total of 15 articles were included on this systematic review describing data of 2566 mono and coinfected patients, 58% male, with mean age was 35.7± 5.7 years. HIV-1 and HTLV-1 coinfected patients were more likely to had shorter survival and faster progression to death or mortality than monoinfected ones. Coinfected had higher CD4 cell counts and less likelihood of ART use. In addition, higher frequency of diseases like ichthyosis (22.2% vs. 6.8%), scabies (5.5% vs. 0%), candidiasis (42% vs. 12%), Strongyloidiasis (15.4% vs. 2%) and neurological manifestations like encephalopathy, peripheral neuropathy and HAM/TSP were more frequently reported in coinfected patients. Conclusions: HIV-1 and HTLV-1 coinfection and HIV-1 and HTLV-1 /2 triple coinfection were related to shorter survival, higher mortality rate, and faster progression to death, while coinfection by HIV-1 / HTLV-2 seems to have neutral association with longer survival, slower AIDS progression, and lower mortality rate. The available evidence indicates an urgent need for prevention and control measures, including screening, diagnosis, and treatment of HIV-1 and HTLV-1/2 coinfected patients. Test-and-treat strategy for patients living with HIV in areas endemic for HTLV infection is mandatory, to avoid the risks of delayed therapy and death for coinfected patients.